Indicators of stress intensity in domestic piglet's vocalisation - Červenková, Iveta (Jihočeská univerzita, 2015)
Vocalizations are widely studied as possible non-invasive indicators of welfare. The most common vocalizations in pigs are grunts and screams. This thesis is focused on the relationship between vocal parameters of piglet's grunts and screams and the behavioural arousal (which is assumed to indicate stress intensity) during the social isolation.
Indicators of stress intensity in domestic piglet's vocalisation
Keywords: vocalization; grunt; scream; piglet; social isolation; arousal